2021
DOI: 10.1093/intqhc/mzab036
|View full text |Cite
|
Sign up to set email alerts
|

Demographics matter: the potentially disproportionate effect of COVID-19 on hospital ratings

Abstract: Background We analyze a sample of 2,816 Medicare-certified acute care hospitals across all US states, using January to December 2019 CMS Hospital Compare datasets merged with county-level socio-demographic data. These data allow us to identify how features of the community in which a hospital serves differentially relate to its patients’ experiences based on the quality of that hospital. Methods A Finite Mixture Model (FMM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Further, we also believe that focusing on top-rated hospitals can be useful if factors associated with performance can be identified and lessons learned can be used by other hospitals. For example, a recent study showed that low-rated hospitals are more likely to face adverse patient experiences due to COVID-19 than high-rated hospitals (Belasen et al, 2021b). An important pathway is to encourage collaboration across the continuum of care and the sharing of information between healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, we also believe that focusing on top-rated hospitals can be useful if factors associated with performance can be identified and lessons learned can be used by other hospitals. For example, a recent study showed that low-rated hospitals are more likely to face adverse patient experiences due to COVID-19 than high-rated hospitals (Belasen et al, 2021b). An important pathway is to encourage collaboration across the continuum of care and the sharing of information between healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…They are important since they directly impact hospitals’ reputation as well as the financial incentives hospitals receive from CMS (Belasen et al. , 2021a, b, c). Furthermore, the association between capacity utilization and patient satisfaction is well established in the literature (Biondi et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has limitations that warrant consideration. Although we controlled for a variety of demographic and clinical factors, it is possible that our data set did not contain any other explanatory factors (23)(24)(25)(26). Given the nature of surveys, which ask respondents to reflect on past events, the potential for recall bias cannot be discounted (27).…”
Section: Discussionmentioning
confidence: 99%